6ER-001 Association between faecal calprotectin values and infliximab trough levels in inflammatory bowel disease patients. (2nd March 2018) - Santacana, E; Padullés, N; Padullés, A; Rodríguez-Alonso, L; Guardiola, J; Bas, J; Esteban-Sánchez, CM; Colom, H
Abstract : Background: Serum infliximab (IFX) trough levels (Cmin) have been associated with clinical response. Therapeutic drug monitoring of IFX has been shown to be clinical and cost effective in inflammatory bowel disease (IBD) patients. However, some patients present clinical symptoms while IFX Cmin >3 mg/L. Activity markers such as faecal calprotectin (FCP) in combination with IFX Cmin could be of clinical utility to optimise therapy in IBD patients. Purpose: To evaluate the relationship between FCP and IFX Cmin, in IBD patients receiving maintenance IFX. Secondary analysis: to determine the use of IFX Cmin as a clinical predictor of FCP <250 mcg/g; and to assess the discriminate ability of FCP to predict subtherapeutic Cmin IFX (Cmin <3 mg/L) by receiver operating characteristic (ROC) curve. Material and methods: Prospective study of IBD patients receiving IFX between January 2014 and February 2017. Patients provided: blood samples drawn immediately before IFX infusion to determine IFX Cmin; and faecal samples within the same IFX cycle of administration to determine FCP. ROC curves were used to assess the discriminative ability of IFX Cmin to predict FCP <250 mcg/g and discriminative ability of FCP to predict IFX Cmin<3 mg/L. Pharmacokinetic and statistical analysis was performed using Nonmem ® 7.3 and SPSS v.19, respectively. Results: Eighty-nine patients (46.1% females/53.9% males) were included. A total of 188 faeces and blood samples were analysed. Median FCP: 233 mcg/g (P25-P75: 77–1225). In 97 samples (51.6%) FCP was <250 mcg/g. Median Cmin: 4.1 mg/L (P25-P75: 1.9–6.9). Median IFX Cmin when FCP <250 mcg/g versus FCP ≥250 mcg/g group was 4.7 mg/L (Cmin ≥3 mg/L: 36%) vs 3.62 mg/L (Cmin ≥3 mg/L: 28%), respectively (p=0.043). The area under the ROC for Cmin IFX to predict FCP <250 mcg/g was 0.586 (95% CI: 0.504 to 0.667) and for FCP to predict Cmin <3 mg/L was 0.596 (95% CI: 0.509 to 0.683). Conclusion: Significantly higher IFX Cmin were observed when FCP<250 mcg/g compared to FCP≥250 mcg/g (4.7 mg/L vs 3.62 mg/L). Also, percentage of samples with Cmin≥3 mg/L is higher when FCP<250 mcg/g vs FCP≥250 mcg/g (36% vs 28%). IFX Cmin was a modest predictor of FCP<250 mcg/g. FCP was a modest biomarker to predict Cmin <3 mg/L. No conflict of interest